Data Governance Facilitate Digital Transformation of Oil and Gas Industry - Su, Jian; Yao, Shanglin; Liu, He (Frontiers in Earth Science, 2022)
Abstract: The data have been increasingly become an important category of strategic resources for enterprises and massive amounts of data with different types involved in the oil and gas industry can be obtained through IoT (Internet of Things) devices. All these devices are supported by the Block Chain technology with characteristics of immutability and credibility in the distributed storage. Finally, the credible data will be rationally used in Big Data analysis and Artificial Intelligence implementation. As the bridge connecting IoT devices, Big Data analysis and Artificial Intelligence implementation, the global mutual trust protocol of Block Chain technology enables effective coordination of participation of multiple parties and ultimately break isolated islands of information. Data governance is a necessary prerequisite for data sharing. It is a basic project to break data islands and business barriers to improve Data Governance capabilities through data sharing for Digital Transformation and high-quality development of the oil and gas industry. From the requirements of Digital Transformation for Data Governance, in this paper the status and problems of Data Governance are recapped with evaluation of Data Governance capabilities of oil and gas companies. A proposal is put forward to apply Block Chain technology to improve the Data Governance system and capabilities as the overall program of the oil and gas industry Data Governance system.